Sumoylation in Synaptic Function and Dysfunction - Schorova, Lenka; Martin, Stéphane (Frontiers in Synaptic Neuroscience, 2016)
Sumoylation has recently emerged as a key post-translational modification involved in many, if not all, biological processes. Small Ubiquitin-like MOdifiers (SUMOs) polypeptides are covalently attached to specific lysine residues of target proteins through a dedicated enzymatic pathway. Disruption of the SUMO enzymatic pathway in the developing brain leads to lethality indicating that this process exerts a central role during embryonic and post-natal development. However, little is still known regarding how this highly dynamic protein modification is regulated in the mammalian brain despite an increasing number of data implicating sumoylated substrates in synapse formation, synaptic communication and plasticity. The aim of this review is therefore to briefly describe the enzymatic SUMO pathway and to give an overview of our current knowledge on the function and dysfunction of protein sumoylation at the mammalian synapse.